Digital inclusion in field schools (Research, Society and Development, 2021)
The present article seeks to understand how computer labs are used and the use of Information and Communication Technologies (TICs) in schools in the countryside of the 17th Regional Education Coordination of the State of Rio Grande do sul. Therefore, its general objective is to analyze how ICTs through the Educational Informatics Laboratories (LIES) are being used as pedagogical support tools in schools in the countryside. Sixteen rural schools were researched. For the development of the research, the case study was sought as a methodological contribution, using questionnaires applied to everyone involved in the process as the data collection instrument, namely: school management team, educators and students, in addition to bibliographic research that sought to understand how the national educational technology program launched by the federal government in 1997 was consolidated, with regard to the implementation of computer labs in schools. The results found point out that there is still a need for training for educators to implement in their pedagogical practices the use of the resources available in the LIES and also the need to maintain the equipment provided by the government.